Raw material type evaluation method for anticorrosive coating on inner wall of demineralized water tank

The test solution was soaked through GC-MS test test sheets and qualitatively analyzing the compounds, which solved the problem that the existing technology failed to effectively evaluate the types of anticorrosion coating materials in the inner wall of the desalinated water tank of the power plant, realized the analysis of the coating sanitary components and the selection of raw materials, and ensured the quality of water quality.

CN119804684APending Publication Date: 2025-04-11NORTH CHINA ELECTRICAL POWER RES INST +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411767874.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The prior art failed to effectively evaluate the types of raw materials for the anticorrosion coating on the inner wall of the desalinated water tank of the power plant, resulting in the unstudy of the dissolution component of the coating in the desalinated water, affecting the water supply quality of the tank.

Method used

The gas chromatography-mass spectrometer (GC-MS) was used to detect the soaking test solution of the coating test piece, and qualitative analysis was performed after extraction and concentration to evaluate the raw material types of the anticorrosion coating.

Benefits of technology

Through GC-MS detection, the compounds in the soaked test solution of the coating test piece can be qualitatively obtained, the types of raw materials of the anticorrosive coating can be evaluated, and the selection of raw materials can be provided to control the dissolving substances and ensure the quality of the effluent of the desalinated water tank.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119804684A_ABST
    Figure CN119804684A_ABST
Patent Text Reader

Abstract

The invention discloses a raw material type evaluation method for an anti-corrosion coating on the inner wall of a desalted water tank. The method comprises the following steps: preparing a coating test piece soaking test solution; detecting the soaking test liquid of the coating test piece by adopting gas chromatography-mass spectrometry; if it is qualitatively obtained that the coating test piece is soaked in the compound in the test liquid, the raw materials of the anticorrosive coating to be evaluated comprise the compound with the molecular weight being 500 or below. According to the invention, the raw material types of the anticorrosive coating on the inner wall of the power plant desalted water tank can be evaluated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for evaluating the raw material types of an anti-corrosion coating on the inner wall of a desalted water tank, belonging to the technical field of evaluation and detection of anti-corrosion coatings. Background Art

[0002] Polyurea is increasingly used in the corrosion protection of the inner wall of desalted water tanks in nuclear power plants and thermal power plants. The dissolution of this polymer organic coating in the desalted water medium has a direct impact on the water quality of the water tank supply. After the desalted water tank inner wall is put into operation with polyurea corrosion protection, if the conductivity and total organic carbon content of the water tank outlet exceed the standard for a long time (more than half a year), it will seriously affect the normal production and operation of the generator set and cause economic losses. The dissolution of the anti-corrosion coating on the inner wall of the desalted water tank of the power plant in the desalted water is an important technical indicator that must be considered in addition to the conventional properties of the coating such as corrosion protection, waterproofing, and anti-aging.

[0003] The dissolution rate detection method of polyurea anticorrosive coating in desalted water tank with total organic carbon (TOC) as the characteristic index was established in the literature such as "Detection of dissolution of polyurea anticorrosive coating in desalted water tank and its influence on water quality" (Xing Chengxia, Chen Weiwei, Hu Yuanxiang, et al. Detection of dissolution of polyurea anticorrosive coating in desalted water tank and its influence on water quality [J]. Electroplating and Finishing, 2022, 41(18): 1333-1337.), "Experimental study and application of dissolution characteristics of anticorrosive coating on inner wall of desalted water tank in power plant" (Xing Chengxia, Li Yongli, Wang Yinggao, et al. Experimental study and application of dissolution characteristics of anticorrosive coating on inner wall of desalted water tank in power plant [J]. Coatings Industry, 2016, 46(1): 63-68.). The polyurea anticorrosive coating specimens from several representative manufacturers were selected, and the TOC dissolution law of the specimens from each manufacturer in desalted water was investigated, and their dissolution rates were measured and compared and analyzed. According to the TOC control value of the desalted water tank in the power plant, the influence of TOC dissolution of polyurea anti-corrosion coatings from various manufacturers on the water quality of the water tank was analyzed. The results show that there is a certain degree of organic matter dissolution in the desalted water from polyurea anti-corrosion coatings, which mainly occurs in the rapid growth period of the initial dissolution stage (1 to 2 weeks). When the dissolution rate is greater than 10μg / (cm 2 ·d), the water quality of the water tank was significantly affected. After this period, the TOC dissolution rate dropped significantly and was less than 2.0μg / (cm 2 ·d), has little impact on the water quality of the water tank.

[0004] Although the above-mentioned prior art has proposed the existence of organic matter dissolution of polyurea coating in desalted water, and has measured the dissolution rate of coating specimens, and proposed a dissolution rate control value in combination with water tank water quality control, it has not studied the components of the dissolution of polyurea coating in desalted water, nor has it evaluated the types of raw materials for the anti-corrosion coating on the inner wall of the desalted water tank of a power plant. Summary of the invention

[0005] In order to solve the above technical problems, the purpose of the present invention is to provide a method for evaluating the raw material type of the anti-corrosion coating on the inner wall of a desalted water tank. The present invention can evaluate the raw material type of the anti-corrosion coating on the inner wall of a desalted water tank in a power plant.

[0006] In order to achieve the above object, the present invention provides a method for evaluating the type of raw materials for the anti-corrosion coating on the inner wall of a desalted water tank, which comprises the following steps:

[0007] (1) Prepare the coating test piece and immerse it in the test solution:

[0008] The anti-corrosion coating test piece to be evaluated is immersed in desalted water to obtain an immersion solution; the total organic carbon content in the immersion solution is determined; if the measured value of the total organic carbon content in the immersion solution is greater than 1.0 mg / L, the immersion solution is used as the coating test piece immersion test solution; if the measured value of the total organic carbon content in the immersion solution is less than 1.0 mg / L, the number of the anti-corrosion coating test pieces to be evaluated immersed in the desalted water is increased so that the measured value of the total organic carbon content in the immersion solution is greater than 1.0 mg / L, and the coating test piece immersion test solution is obtained;

[0009] (2) Using gas chromatography-mass spectrometry to detect the coating test piece immersed in the test liquid:

[0010] The coating test piece obtained in step (1) is immersed in the test liquid for extraction and concentration to obtain a sample to be tested; the sample to be tested is tested by gas chromatography-mass spectrometry, and the compounds in the test liquid immersed in the coating test piece are qualitatively obtained by using the test result;

[0011] (3) Evaluate the types of raw materials for anti-corrosion coatings:

[0012] If the compounds in the test solution in which the coating test piece is immersed are qualitatively determined in step (2), then the raw materials of the anti-corrosion coating to be evaluated include compounds with a molecular weight of less than 500.

[0013] According to a specific embodiment of the present invention, preferably, in step (1), the desalted water is ultrapure water, and its resistivity is 18.2 MΩ.

[0014] According to a specific embodiment of the present invention, preferably, in step (1), the anti-corrosion coating test piece to be evaluated is immersed in deionized water for more than 7 days. The immersion temperature may be room temperature (25±5° C.).

[0015] According to a specific embodiment of the present invention, preferably, in step (1), the ratio of the total surface area of ​​the anti-corrosion coating test piece to be evaluated immersed in deionized water to the volume of the deionized water (i.e., the surface-to-volume ratio) is 0.2 cm -1The above. A person skilled in the art can adjust the number and size of the anti-corrosion coating test pieces to be evaluated, and adjust the volume of the desalted water based on the above surface-to-volume ratio, as long as the surface-to-volume ratio range is met. And, if multiple test pieces are used, the surface area of ​​the test piece is the total surface area of ​​all the test pieces. In addition, the volume of the desalted water can be 500 to 1000 mL.

[0016] According to a specific embodiment of the present invention, preferably, in step (1), the preparation steps of the anti-corrosion coating specimen to be evaluated include: spraying the coating on the surface of the template to form a coating; curing the coating for 24 hours after formation, and then demolding without using a release agent to obtain a demolded coating; curing the demolded coating for more than 30 days to obtain the anti-corrosion coating specimen to be evaluated.

[0017] According to a specific embodiment of the present invention, preferably, in step (1), the anti-corrosion coating test piece to be evaluated is immersed in desalted water until the total organic carbon content in the immersion liquid reaches equilibrium, thereby obtaining a coating test piece immersion test liquid. It can be understood by those skilled in the art that the total organic carbon content in the immersion liquid reaches equilibrium, which means that multiple sampling tests are performed at appropriate intervals, and when the total organic carbon content obtained by the test is substantially unchanged, the total organic carbon content in the immersion liquid reaches equilibrium.

[0018] According to a specific embodiment of the present invention, preferably, in step (1), the total organic carbon content in the soaking liquid can be determined by the total organic carbon content determination method described in ASTM D5904-2009 "Test method for total carbon content, organic carbon and inorganic carbon in water by ultraviolet light, persulfate oxidation and thin film conductivity detection", or it can be determined by other methods such as spectrophotometry.

[0019] According to a specific embodiment of the present invention, preferably, in step (2), extracting and concentrating the coating test piece immersed in the test liquid obtained in step (1) comprises: extracting the coating test piece immersed in the test liquid with dichloromethane to obtain an extract; and then concentrating the extract with a nitrogen blowing concentrator to obtain a concentrated solution, which is the sample to be tested.

[0020] Specifically, soaking the coating test piece obtained in step (1) in the test liquid for extraction and concentration comprises:

[0021] Extraction: Use a pipette to transfer 100mL of the coating test piece to soak the test solution, put it into a 500mL separatory funnel, add 20mL of dichloromethane for extraction, shake it sufficiently and let it stand for stratification, dehydrate the organic phase obtained after stratification through a funnel filled with anhydrous sodium sulfate, then collect the dehydrated organic phase in a concentration bottle, add 20mL of dichloromethane for extraction (to ensure complete extraction), collect the organic phase, and then repeatedly wash the separatory funnel and anhydrous sodium sulfate 2 to 3 times with an appropriate amount of dichloromethane, combine the organic phases to obtain an extract;

[0022] Concentration: At room temperature, the extract was concentrated using a nitrogen blowing concentrator. The nitrogen was blown until there was airflow fluctuation on the surface of the extract (to avoid the formation of air vortices). The wall of the concentration bottle exposed during the nitrogen blowing process was washed with dichloromethane several times. The extract was concentrated to 5 mL to obtain a concentrated solution, which was the sample to be tested.

[0023] According to a specific embodiment of the present invention, preferably, in step (2), the preparation step of the blank sample used for detection by gas chromatography-mass spectrometry includes: taking 100 mL of first-grade water with a pipette, extracting and concentrating according to the above steps, mixing and fixing the volume.

[0024] According to a specific embodiment of the present invention, preferably, in step (2), the gas chromatograph-mass spectrometer includes a Thermo Fisher Trace1300 ISQQD gas chromatograph-mass spectrometer, and the chromatographic column used includes a capillary chromatographic column DB-5MS, and the size of the chromatographic column is 30m×0.25mm×0.25μm.

[0025] According to a specific embodiment of the present invention, preferably, in step (2), the conditions of gas chromatography include: the carrier gas is helium, the carrier gas flow rate is 1.0 mL / min, and the flow is constant; the injection port temperature is 280°C, the injection port mode is splitless, and the injection volume is 1.0 μL; the chromatographic column heating program includes: maintaining at 35°C for 2 min, then heating to 150°C at a rate of 15°C / min, maintaining at 150°C for 5 min, then heating to 290°C at a rate of 3°C / min, and maintaining at 290°C for 5 min.

[0026] According to a specific embodiment of the present invention, preferably, in step (2), the mass spectrometry conditions include: the electron bombardment source is an EI source, the ionization energy is 70eV, the transmission line temperature is 280°C, the ion source temperature is 250°C, the mass scanning range is 35-450amu, the solvent delay time is 5min, and the scanning mode is a full scan scan mode. The present invention adopts a full scan scan mode, and the mass range of the scan covers the mass of the molecular ions and fragment ions of the measured compound, and the full spectrum of the compound can be obtained, which is convenient for subsequent retrieval and qualitative analysis of the NIST mass spectrum library.

[0027] According to a specific embodiment of the present invention, preferably, in step (2), the compounds in the test solution in which the coating test piece is immersed are qualitatively obtained using the test results, including:

[0028] a. Screen out compounds whose peak area in the total ion flow chart detected is greater than 1.0%;

[0029] b. Match the detected mass spectrum with the standard mixture in the NIST mass spectrum library to screen out compounds with a similarity of more than 70%;

[0030] c. comparing the retention time of the compound in the total ion flow chart obtained by the detection with the retention time of the standard compound under the same chromatographic conditions, and screening out compounds with a retention time deviation of less than 1%;

[0031] d. The compounds with a peak area ratio greater than 1.0% in step a, the compounds screened out in step b, or the compounds screened out in both step b and step c are taken as valid results of qualitative analysis.

[0032] The present invention has the following beneficial effects:

[0033] The present invention proposes a method for evaluating the raw material types of the anti-corrosion coating on the inner wall of a desalted water tank. The GC-MS combination is used for detection, and the compounds in the test solution immersed in the coating test piece can be qualitatively obtained, thereby evaluating the raw material types of the anti-corrosion coating. The present invention uses GC-MS combination to detect the coating test piece immersed in the test solution, and further controls the conditions of gas chromatography and mass spectrometry within the above range. It has high sensitivity and can detect the amount of substances at the ng / g (10-9) level; and the analysis speed is fast, and a test piece can be analyzed within a few minutes or tens of minutes; at the same time, the separation efficiency is high, and organic homologues, complex compounds, isomers, and chiral isomers can be analyzed. The raw material type evaluation results obtained by the present invention can be used to obtain the analysis results of the dissolution components of anti-corrosion coatings such as polyurea in the desalted water tank of a power plant, which has guiding significance for the selection of raw materials for anti-corrosion coatings such as polyurea, and can control the dissolution of the anti-corrosion coating to ensure that the water quality of the desalted water tank meets the requirements. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 The infrared spectrum and matching diagram of the dried sample of the coating test piece immersed in the test liquid in Example 1.

[0035] Figure 2 This is the H NMR spectrum of the coating specimen in Example 1 immersed in the test solution.

[0036] Figure 3a This is the total ion current diagram of the GC-MS measurement in Example 1.

[0037] Figure 3b This is the mass spectrum with a retention time of 13.90 min measured by GC-MS in Example 1.

[0038] Figure 3c This is the mass spectrum with a retention time of 15.85 min measured by GC-MS in Example 1.

[0039] Figure 3d This is the mass spectrum with a retention time of 17.53 min measured by GC-MS in Example 1.

[0040] Figure 3e This is the mass spectrum with a retention time of 19.73 min measured by GC-MS in Example 1.

[0041] Figure 3f This is the mass spectrum with a retention time of 20.34 min measured by GC-MS in Example 1. DETAILED DESCRIPTION

[0042] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the present invention is now described in detail below, but it should not be construed as limiting the scope of implementation of the present invention.

[0043] It should be noted that, unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as commonly understood by one of ordinary skill in the art to which the present invention belongs.

[0044] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0045] It should be understood that the terms "comprises," "comprising" and / or "containing" when used herein specify the presence of stated features, integers, steps, components or combinations thereof, but do not preclude the presence or addition of one or more other features, integers, steps, components or combinations thereof.

[0046] The endpoints and any values ​​of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.

[0047] Example 1

[0048] This embodiment provides a method for evaluating the type of raw materials for the anti-corrosion coating on the inner wall of a desalted water tank.

[0049] The instruments and equipment used in this example are:

[0050] Sievers T900 total organic carbon analyzer, GE, USA; Nicolet IS5 Fourier transform infrared spectrometer, Thermo, USA; AVAVCE 400 nuclear magnetic hydrogen spectrometer, Bruker, Germany; Trace1300ISQQD gas chromatograph-mass spectrometer, Thermo Fisher Scientific, USA.

[0051] Preparation of anti-corrosion coating test pieces to be evaluated:

[0052] According to the ratio and parameter requirements of the coating raw materials, the coating is sprayed on the template using special spraying equipment. The template should be flat, clean and smooth, and no release agent is used to prevent additional organic pollution to the coating sample. After the coating is formed, it is demoulded after curing for 24 hours. After demoulding, it is continued to be cured for at least 30 days to obtain the test piece. The template used should be flat, clean and smooth. The curing conditions are: room temperature (25±5℃).

[0053] Test piece processing:

[0054] According to the above method, a polyurea anti-corrosion coating test piece for a certain type of power plant desalted water tank was prepared, the test piece specifications were 100mm×20mm×1.5mm, and the number was 20. The dirt on the surface of the test piece was removed, and it was rinsed repeatedly to ensure that the test piece was clean.

[0055] Prepare coating test pieces and immerse them in test solution:

[0056] The water used for immersion of the test piece is demineralized water from a power plant, which is ultrapure water produced by a laboratory water purifier with a resistivity of 18.2 MΩ.

[0057] Prepare a PE material chromatography grade sampling bottle with an effective volume of 1L, and wash and soak it repeatedly to ensure that the sampling bottle is clean and pollution-free. Pour 1L of ultrapure water into the sampling bottle and soak 20 test pieces in the bottle. Under room temperature conditions, soak the test pieces in water for at least 30 days. Sample and test the TOC content of the soaking liquid on the 1st, 3rd, 5th and 7th day after soaking. After the 7th day, sample and measure once a week. After each sampling (sampling volume is 12.5mL), add the same volume of soaking water to the soaking liquid to keep the total volume of the soaking liquid unchanged. The test is terminated when the TOC measurement value of the soaking liquid reaches equilibrium. After testing, the TOC equilibrium concentration of the test piece soaking liquid is 74.7mg / L, and the equilibrium time is 30d. The test piece soaking liquid at this time is used as the coating test piece soaking test liquid. Among them, the TOC content of the soaking liquid is obtained by testing with a total organic carbon analyzer.

[0058] Detection method:

[0059] As a comparison, Fourier transform infrared spectroscopy (FT-IR) and nuclear magnetic resonance spectroscopy (NMR) were used for detection. In addition, as a comparison, a variety of sample pretreatment methods (headspace injection, thermal pyrolysis, liquid extraction and concentration) combined with gas chromatography mass spectrometry (GC-MS) were used. Among them, headspace injection and thermal pyrolysis were used as comparisons. Among them, the main detection conditions of GC-MS are as follows:

[0060] 1. Equipment and utensils:

[0061] Thermo Fisher Trace1300 ISQQD gas chromatograph-mass spectrometer (with autosampler);

[0062] Chromatographic column: capillary column DB-5MS 30m×0.25mm×0.25μm;

[0063] Nitrogen blowing concentrator;

[0064] Nitrogen (steel cylinder, 99.999%);

[0065] Separatory funnel;

[0066] pipette;

[0067] 2. Reagents:

[0068] Dichloromethane: chromatographic grade;

[0069] Experimental water: laboratory grade one water;

[0070] Anhydrous sodium sulfate: high purity.

[0071] 3. Sample pretreatment:

[0072] Extraction: Use a pipette to transfer 100mL of the coating test piece soaked in the test solution into a 500mL separatory funnel, add 20mL of dichloromethane for extraction, shake thoroughly, let stand for stratification, and dehydrate the organic phase obtained after stratification through a funnel filled with an appropriate amount of anhydrous sodium sulfate. Collect the dehydrated organic phase in a concentration bottle, add 20mL of dichloromethane for extraction (to ensure complete extraction), collect and combine the organic phases, wash the funnel and the sodium sulfate layer repeatedly with a small amount of dichloromethane 2 to 3 times, combine the organic phases, and obtain the extract for concentration.

[0073] Concentration: At room temperature, use a nitrogen blowing concentrator to concentrate the extract. Turn on the nitrogen until there is airflow fluctuation on the surface of the extract (to avoid the formation of air vortices). Use dichloromethane to wash the concentrator wall exposed during the nitrogen blowing process several times. Concentrate the extract to about 5mL to obtain a concentrated solution. Transfer all of it to 10mL and mix well to obtain the sample to be tested.

[0074] On-line: Transfer an appropriate amount of the sample to be tested into a 1.5 mL injection bottle, place it in the automatic injection tray of the gas chromatograph-mass spectrometer, and obtain the total ion flow diagram and mass spectrum by on-line detection.

[0075] Blank sample: Use a pipette to transfer 100 mL of first-grade water, extract and concentrate according to the above steps, mix and fix the volume, transfer to a 1.5 mL injection bottle, put it into the automatic injection plate of the gas chromatography-mass spectrometry instrument, and detect it on the instrument.

[0076] 4. Chromatography mass spectrometry conditions:

[0077] 1) Gas chromatography conditions:

[0078] Carrier gas: helium, flow rate 1.0 mL / min (constant flow);

[0079] Inlet temperature and mode: 280 °C, splitless;

[0080] Injection volume: 1.0 μL;

[0081] Column heating program: maintain at 35°C for 2 min, increase the temperature to 150°C at 15°C / min, maintain for 5 min, then increase the temperature to 290°C at 3°C / min, maintain for 5 min.

[0082] 2) Mass spectrometry conditions:

[0083] Electron bombardment source: EI source;

[0084] Ionization energy: 70eV;

[0085] Transmission line temperature: 280°C;

[0086] Ion source temperature: 250°C,

[0087] Mass scanning range: 35-450amu;

[0088] Solvent delay time: 5min;

[0089] Scan mode: Full scan mode. The mass range scanned in Scan mode covers the mass of the molecular ion and fragment ion of the tested compound, and the full spectrum of the compound can be obtained, which is convenient for subsequent retrieval and qualitative analysis of the NIST mass spectrum library.

[0090] 5. Data processing:

[0091] a. Screen out compounds whose peak area in the total ion flow chart detected is greater than 1.0%;

[0092] b. Match the detected mass spectrum with the standard mixture in the NIST mass spectrum library to screen out compounds with a similarity of more than 70%;

[0093] c. comparing the retention time of the compound in the total ion flow chart obtained by the detection with the retention time of the standard compound under the same chromatographic conditions, and screening out compounds with a retention time deviation of less than 1%;

[0094] d. The compounds with a peak area ratio greater than 1.0% in step a, the compounds screened out in step b, or the compounds screened out in both step b and step c are taken as valid results of qualitative analysis.

[0095] Specifically, the total ion current is automatically integrated to give the retention time, peak area, peak height and proportion, and the molecular ion peaks given in the mass spectrum are searched by the NIST mass spectral library using the Thermo Fisher data processing software to obtain the most similar compounds for each peak, give the similarity, and select the closest substance.

[0096] The spectrum obtained by library search matches the standard spectrum. Whether it is true or not, it should be analyzed:

[0097] (1) The volatile point of the compound in GC / MS separation is correct (check the chemical manual) before confirmation;

[0098] (2) When GC / MS is separated, the low volatility compound and the high volatility compound have the same library search graph, which means they are definitely not the same compound; it is possible that a pyrolysis product at high temperature has the same spectrum as the low volatility compound, which often occurs in the analysis of high-carbon aliphatic hydrocarbons;

[0099] (3) Several spectra with similar retention times are from the same library search results and are likely to be isomers, which can be distinguished by retention time.

[0100] The test results of this example and the comparative FT-IR test results and NMR test results are described as follows.

[0101] FT-IR test results:

[0102] Take 500mL of coating test piece, soak it in the test solution and dry it at 105℃. Then use potassium bromide tablet pressing method to press the dried sample into test piece and carry out FT-IR detection. The infrared spectrum and matching diagram are shown in Figure 1 shown.

[0103] Depend on Figure 1 It can be seen that at wave numbers 400 to 4 000 cm -1 Within the scanning range, the infrared spectra of the sample and the background (KBr) are basically consistent, and no organic functional groups present in the sample of the coating specimen immersed in the test liquid are detected. The main reason is that the organic content in the dried sample is too low, which is below the detection limit of the FT-IR method.

[0104] NMR test results:

[0105] Take a small amount of coating test piece and soak it in the test solution, add a small amount of deuterated water, mix it and place it in the NMR tube, and test it on the machine. Its NMR hydrogen spectrum (D2O) is as follows Figure 2 shown.

[0106] Figure 2 Only the background (D2O) peak was detected, and no other organic group peaks were detected. The organic content in the test solution immersed in the coating specimen was low, and no organic groups were detected by nuclear magnetic resonance spectroscopy.

[0107] It can be seen that both FT-IR and NMR are not suitable for detecting the dissolution of the anti-corrosion coating on the inner wall of the desalted water tank of the present invention.

[0108] GC-MS test results:

[0109] No valid information was obtained from direct GC-MS, HS-GCMS (headspace sampling-GCMS) and Py-GCMS (pyrolysis-GCMS) measurements of the coating specimens immersed in the test solution, indicating that the coating specimens immersed in the test solution did not contain volatile and high-boiling-point large molecular weight organic matter.

[0110] After the coating specimens were immersed in the test solution and extracted and concentrated by the above method, GC-MS was used to obtain effective information on multiple organic components in the immersion solution. The results are as follows: Figure 3a (Total Ion Current), Figure 3b (Mass spectrum with retention time of 13.90min), Figure 3c (Mass spectrum with retention time of 15.85min), Figure 3d (Mass spectrum with retention time of 17.53min), Figure 3e (Mass spectrum with retention time of 19.73min) and Figure 3f (Mass spectrum with retention time of 20.34min). Figures 3a to 3f The SPME-GC-MS spectra of organic matter in the test solution of the coating test piece are shown. It can be seen that the sample pretreatment method of extraction and concentration of the present invention can obtain accurate results, while the sample pretreatment methods such as headspace sampling and thermal cracking are not suitable for the detection of the dissolution of the anti-corrosion coating on the inner wall of the desalted water tank of the present invention.

[0111] Depend on Figure 3a It can be seen that peaks with a peak area ratio greater than 10% appeared at several different retention time points. Figure 3b to Figure 3fThe following are the mass spectra of the peak substances at different retention times. According to the NIST mass spectrum library search and analysis, the peak substances include propylene carbonate, triethyl phosphate, 2,4-di-tert-butylphenol, tris(2-chloropropyl) phosphate and 1,3,5-triphenylcyclohexane. The retention time and peak area percentage of each substance are shown in Table 1 below. In addition, trace components with a peak area percentage of less than 10% were also detected, including hexanoic acid, 2,6-dimethylbenzaldehyde, isooctanoic acid and other organic substances with a molecular weight of less than 500.

[0112] Table 1 Qualitative analysis results of main components of organic matter in the coating test piece immersed in the test solution

[0113]

[0114] From the quantitative analysis results in Table 1, it can be seen that the components with higher organic extractable contents in the test solution in which the coating specimens are immersed are tris(2-chloropropyl) phosphate, triethyl phosphate and propylene carbonate, and their roles in the coating raw materials used are shown in Table 2.

[0115] Table 2 Effect of dissolution in the test piece raw materials

[0116]

[0117] The roles of these organic dissolutions in the test piece raw materials are flame retardants, diluents or solvents, and antioxidants. Combined with the quantitative detection results of total organic carbon in the immersion solution, the largest dissolution amounts are phosphate flame retardants and diluents or organic solvents. These dissolutions are all small molecular organic matter. Because they do not participate in the synthetic chemical reaction of polyurea, they are in a free state in the coating. When the coating is immersed in deionized water for a long time, it is easy to migrate outward from the coating surface or a certain depth of the surface and dissolve.

[0118] Therefore, since the compounds in the test solution immersed in the coating test piece are qualitatively obtained, the raw materials of the anti-corrosion coating evaluated in this embodiment include compounds with a molecular weight of 500 or less.

[0119] Example 2

[0120] After the anti-corrosion coating was applied to the inner wall of a desalted water tank in a power plant, the flushing water was taken as a water sample during the water injection and flushing stage (i.e., as the test liquid for immersing the coating test piece). The method in Example 1 was used to determine the organic extractables of the coating. The determination results are shown in 3 below.

[0121] Table 3 Determination results of organic extracts from coatings

[0122]

[0123]

[0124] In Table 3, the greater the peak area ratio, the higher the content of the compound. Since the compounds in the test solution immersed in the coating test piece are qualitatively obtained, the raw materials of the anti-corrosion coating evaluated in this embodiment include compounds with a molecular weight of 500 or less.

[0125] Example 3

[0126] The method in Example 1 was used to measure the organic extracts of various types of anti-corrosion coatings. The measurement results are shown in Table 4 below.

[0127] Table 4 Determination results of organic leaching of different types of coatings

[0128]

[0129]

[0130]

[0131]

[0132] The compounds with a peak area ratio greater than 1% listed in Table 4 are coating extracts, which are used as effective results of qualitative analysis. Since the various types of coatings tested in this embodiment are qualitatively obtained by immersing the coating test pieces in the test solution, the raw materials of the various types of anti-corrosion coatings evaluated in this embodiment all include compounds with a molecular weight of less than 500.

Claims

1. A method for evaluating the type of raw materials for the anti-corrosion coating on the inner wall of a desalted water tank, comprising the following steps: (1) Prepare the coating test piece and immerse it in the test solution: The anti-corrosion coating test piece to be evaluated is immersed in desalted water to obtain an immersion solution; the total organic carbon content in the immersion solution is determined; if the measured value of the total organic carbon content in the immersion solution is greater than 1.0 mg / L, the immersion solution is used as the coating test piece immersion test solution; if the measured value of the total organic carbon content in the immersion solution is less than 1.0 mg / L, the number of the anti-corrosion coating test pieces to be evaluated immersed in the desalted water is increased so that the measured value of the total organic carbon content in the immersion solution is greater than 1.0 mg / L, and the coating test piece immersion test solution is obtained; (2) Using gas chromatography-mass spectrometry to detect the coating test piece immersed in the test liquid: The coating test piece obtained in step (1) is immersed in the test liquid for extraction and concentration to obtain a sample to be tested; the sample to be tested is tested by gas chromatography-mass spectrometry, and the compounds in the test liquid immersed in the coating test piece are qualitatively obtained by using the test result; (3) Evaluate the types of raw materials for anti-corrosion coatings: If the compounds in the test solution in which the coating test piece is immersed are qualitatively determined in step (2), then the raw materials of the anti-corrosion coating to be evaluated include compounds with a molecular weight of less than 500.

2. The method for evaluating the raw material types of the anti-corrosion coating on the inner wall of a desalted water tank according to claim 1, wherein: In step (1), the desalted water is ultrapure water, and its resistivity is 18.2 MΩ.

3. The method for evaluating the raw material types of the anti-corrosion coating on the inner wall of a desalted water tank according to claim 1, wherein: In step (1), the anti-corrosion coating test piece to be evaluated is immersed in desalted water for more than 7 days.

4. The method for evaluating the raw material types of the anti-corrosion coating on the inner wall of a desalted water tank according to claim 1, wherein: In step (1), the ratio of the total surface area of ​​the anti-corrosion coating specimen to be evaluated immersed in deionized water to the volume of the deionized water is 0.2 cm -1 above.

5. The method for evaluating the raw material types of the anti-corrosion coating on the inner wall of a desalted water tank according to claim 1, wherein: In step (1), the preparation steps of the anti-corrosion coating specimen to be evaluated include: spraying the coating on the surface of the template to form a coating; curing the coating for 24 hours after the coating is formed, and then demolding without using a release agent to obtain a demolded coating; curing the demolded coating for more than 30 days to obtain the anti-corrosion coating specimen to be evaluated.

6. The method for evaluating the raw material types of the anti-corrosion coating on the inner wall of a desalted water tank according to claim 1, wherein: In step (1), the anti-corrosion coating specimen to be evaluated is immersed in deionized water until the total organic carbon content in the immersion solution reaches equilibrium, thereby obtaining a coating specimen immersion test solution.

7. The method for evaluating the raw material types of the anti-corrosion coating on the inner wall of a desalted water tank according to claim 1, wherein: In step (2), extracting and concentrating the test solution soaked in the coating test piece obtained in step (1) includes: extracting the test solution soaked in the coating test piece with dichloromethane to obtain an extract; and then concentrating the extract with a nitrogen blowing concentrator to obtain a concentrated solution, which is the sample to be tested; Preferably, soaking the coating test piece obtained in step (1) in the test liquid for extraction and concentration comprises: Extraction: Use a pipette to transfer 100mL of the coating test piece to soak the test solution, put it into a 500mL separatory funnel, add 20mL of dichloromethane for extraction, shake it fully and let it stand for stratification, then dehydrate the organic phase obtained after stratification through a funnel filled with anhydrous sodium sulfate, then collect the dehydrated organic phase in a concentration bottle, add 20mL of dichloromethane for extraction, collect the organic phase, then wash the separatory funnel and anhydrous sodium sulfate repeatedly with an appropriate amount of dichloromethane 2 to 3 times, combine the organic phases to obtain an extract; Concentration: At room temperature, the extract was concentrated using a nitrogen purge concentrator. The nitrogen was blown until there was airflow fluctuation on the surface of the extract. The wall of the concentration bottle exposed during the nitrogen purge was washed with dichloromethane several times. The extract was concentrated to 5 mL to obtain a concentrated solution, which was the sample to be tested.

8. The method for evaluating the raw material types of the anti-corrosion coating on the inner wall of a desalted water tank according to claim 1, wherein: In step (2), the gas chromatograph-mass spectrometer includes a Thermo Fisher Trace1300 ISQQD gas chromatograph-mass spectrometer, and the chromatographic column used includes a capillary chromatographic column DB-5MS, and the size of the chromatographic column is 30m×0.25mm×0.25μm.

9. The method for evaluating the type of raw materials for the anti-corrosion coating on the inner wall of a desalted water tank according to claim 8, wherein: In step (2), the gas chromatography conditions include: the carrier gas is helium, the carrier gas flow rate is 1.0 mL / min, constant flow; the injection port temperature is 280°C, the injection port mode is splitless, and the injection volume is 1.0 μL; the chromatographic column temperature program includes: maintaining at 35°C for 2 minutes, then heating to 150°C at a rate of 15°C / min, maintaining at 150°C for 5 minutes, then heating to 290°C at a rate of 3°C / min, and maintaining at 290°C for 5 minutes; Preferably, in step (2), the mass spectrometry conditions include: the electron bombardment source is an EI source, the ionization energy is 70 eV, the transmission line temperature is 280°C, the ion source temperature is 250°C, the mass scanning range is 35-450 amu, the solvent delay time is 5 min, and the scanning mode is a full scan scan mode.

10. The method for evaluating the raw material types of the anti-corrosion coating on the inner wall of a desalted water tank according to claim 1, wherein: In step (2), the compounds in the test solution in which the coating test piece is immersed are qualitatively determined using the test results, including: a. Screen out compounds whose peak area in the total ion flow chart detected is greater than 1.0%; b. Match the detected mass spectrum with the standard mixture in the NIST mass spectrum library to screen out compounds with a similarity of more than 70%; c. comparing the retention time of the compound in the total ion flow chart obtained by the detection with the retention time of the standard compound under the same chromatographic conditions, and screening out compounds with a retention time deviation of less than 1%; d. The compounds with a peak area ratio greater than 1.0% in step a, the compounds screened out in step b, or the compounds screened out in both step b and step c are taken as valid results of qualitative analysis.